Pengaruh Kompetensi, Independensi Auditor dan Due Professional Care terhadap Kualitas Audit pada Kantor Akuntan Publik di Jakarta - Savitri Ajiningtias Prasetyo; Kenny Ardillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of Competence, Auditor Independence, and Due Professional Care on Audit Quality at Public Accounting Firms in Jakarta. Processing data in this study using quantitative methods. The hypothesis testing method uses multiple linear regression analysis method. The results showed that competence had a significant effect on audit quality, auditor independence had a significant effect on audit quality, and due professional care had a significant effect on audit quality.